From Respiration to Fleshpiration: A Merleau-Pontian Journey into Respiratory Philosophy and Respiratory Religion with Jesus, St. Paul, Claudel, and Merleau-Ponty - Berndtson, Petri (Poligrafi, 2023)
In this article, I introduce a new word, the neologism “fleshpiration.” It is a word or a name in which I intertwine “flesh” and “spirit” or “spiration.” This new word is inspired by the thinking of Jesus, St. Paul, Paul Claudel, and Maurice Merleau-Ponty. The interpretative starting point of my article is taken from Claudel, who states: “the spirit is respiration.” With Claudel’s idea, which has its roots in the etymological analysis of pneuma and spiritus, I interpret the spirit (pneuma) of Jesus and St. Paul to mean respiration in the first place. Within this respiratory interpretative context, I suggest that both Jesus and St. Paul emphasised the essentiality of breathing in their religious thinking. For St. Paul, life according to the flesh and life according to the Spirit as life according to the Respiration are opposite lifestyles. Within the context of Merleau-Ponty, it can be said that St. Paul’s dichotomy between the flesh and the Spirit can be challenged and surpassed. For Merleau-Ponty, the flesh and the Spirit can be intertwined in a paradoxical manner. Within this framework of paradoxical thinking, it becomes possible to discover this new word “fleshpiration” and initially claim that it names a new respiratory beginning for philosophy and religion.